Art as a language for autism building effective therapeutic relationships with children and adolescents - Richardson, Jane Ferris (New York Routledge, Taylor & Francis Group, 2023)
"Art as a Language for Autism addresses the clinical challenges that are common in working with autistic spectrum disorder by exploring how artistic expression can provide a communicative language for younger clients who are set in their thought processes and preferences. Exploring how both art and play-based approaches can be effective tools for engaging therapeutic work, this book introduces strategies to help young patients find expressive "languages" that can fully support communication, expression, and empathic understanding, as well as build skills for relaxation, calming, and coping. Building from a foundation of a patient's individual strengths and interests, this playful and integrative approach is informed by an awareness of the individual sensory profiles and the developmental needs of children and adolescents with autism. Through a greater awareness of these materials and processes for therapy, the reader will be able to create a space for their young clients to share what they know and care about. This exciting new book is essential reading for clinicians working with children and adolescents on the autism spectrum"--
Includes bibliographical references and index.
Keywords: Art therapy for children; Art therapy for teenagers; Autism in adolescence -- Treatment; Autism in children -- Treatment